Early Implementation of Augmentative and Alternative Communication Supports in Preschool Children with Autism Spectrum Disorder: A Multi-Professional Perspective - Syriopoulou - Delli, Christine K.; Paraskeva, Eirini (Eximia, 2025)
The purpose of this study was to examine the relationship between the early use of Augmentative and Alternative Communication (AAC) strategies and expressive communication outcomes of preschool-aged children with Autism Spectrum Disorder (ASD). The analysis of the data showed that use of AAC was statistically significantly associated with estimated improvement in communication and expressive skills (Mann Whitney U = 48.000, p < 0.001). Also, a positive association was found between initial level of spoken language and success of the intervention (Spearman p = 0.260, p = 0.001), demonstrating the need for methods to be individualized. According to participants, the PECS method was the most effective form of ECE, while many practitioners reported the frequent use of non-verbal modes of communication such as gaze and gestures. Results suggest that the early introduction of AAC may facilitate the development of expressive communication skills in preschool aged children who have been diagnosed with ASD.